Fundamentals of voice-quality engineering in wireless networks - Perry, Avi; Cambridge (Online service). (Cambridge Cambridge University Press, 2006)
Network operators are faced with the challenge of maximizing the quality of voice transmissions in wireless communications without impairing speech or data transmission. This book provides a comprehensive survey of voice quality algorithms, features, interactions, and trade-offs, at the device and system level. Using a practitioner rather than algorithm-designer angle, this book is unique. It elaborates on the root cause of impairments and ways for resolving them, as well as methodologies for measuring and quantifying voice quality before and after applying the remedies. The key issues are exemplified using case studies. Avoiding complex mathematics, the approach is based on real and sizable field experience supported by scientific and laboratory analysis. This title is suitable for practitioners in the wireless communications industry and graduate students in electrical engineering.
Electronic reproduction.
Keywords: Vocoder; Wireless communication systems; Speech processing systems; Electronic books